Power ultrasound decontamination of wastewater from fresh-cut lettuce washing for potential water recycling. (December 2015) - Anese, Monica; Maifreni, Michela; Bot, Francesca; Bartolomeoli, Ingrid; Nicoli, Maria Cristina
Abstract: The decontamination effect of pulsed and continuous power ultrasound, provided at either controlled or uncontrolled temperature regimes, was studied with reference to native microflora and inoculated pathogenic bacteria in wastewater obtained by fresh-cut lamb's lettuce washing. Results showed that decontamination efficacy increased with increasing specific energy and was higher when ultrasound treatment was provided under uncontrolled temperature regime. Continuous ultrasound supplied without temperature control allowed to achieve 3.2 Log reductions of native microflora during 20 min treatment, while 5 Log reductions of inoculated Listeria monocytogenes, Escherichia coli and Salmonella enterica were attained within 5 min of ultrasonication. The heat generated during continuous ultrasound accounted for approximately 58% of the total decontamination effect against L. monocytogenes, while it contributed for 100% to E. coli and S. enterica inactivation. Industrial relevance: The application of power ultrasound combined with in situ generated heat could represent an effective tool for water decontamination and recycling in the fresh-cut industry. In addition, besides safety requirements, this technology would also meet cost-effectiveness criteria and existing standards. Highlights: Power ultrasound decontamination efficacy increased with increasing specific energy. Ultrasound associated with in situ generated heat disinfected wash water efficiently. Synergy between power ultrasound and heat was found. Ultrasound-heat combination can be used for recycling water from fresh-cut industry.